Preparation method of high-performance aluminum oxide ceramic substrate

By adding sintered core material, polyacrylic acid and composite adhesive to the preparation of alumina ceramic substrates, a macromolecular chain liquid phase system is formed, which solves the problems of limited strength, high warpage and roughness of traditional alumina ceramic substrates. The mechanical strength and thermal conductivity of the ceramic substrate have been significantly improved.

CN119462087APending Publication Date: 2025-02-18HUBEI HUAQING NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411528651.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-18

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The preparation method of the high-performance aluminum oxide ceramic substrate comprises the following steps: S1, mixing and dispersing: carrying out ball milling and dispersing on polyacrylic acid, a sintered core material, a composite adhesive and aluminum oxide to obtain mixed slurry; s2, tape casting, sheet arranging and flattening treatment and rubber discharging are conducted; S3, sintering is conducted, specifically, materials obtained after rubber discharging are fed into a discharge plasma sintering furnace to be heated to the temperature of 1550-1650 DEG C, and heat preservation is conducted for 30-50 min; and S4, cooling: cooling the sintered body to normal temperature. According to the preparation method of the high-performance aluminum oxide ceramic substrate, the obtained ceramic substrate has good mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a method for preparing a high-performance alumina ceramic substrate. Background Art

[0002] At present, the commonly used substrate materials mainly include plastic substrates, metal substrates, ceramic substrates and composite substrates. Ultra-thin composite substrates made of advanced ceramic materials have excellent electrical insulation properties, high thermal conductivity, excellent soft solderability and high adhesion strength, and can be etched with various patterns like PCB boards, and have great current carrying capacity. Ceramic substrates are much better than ordinary glass fiber PCB boards due to their heat dissipation performance, current carrying capacity, insulation, thermal expansion coefficient, etc., and are widely used in high-power power electronic modules, aerospace, military electronics and other products. Traditional alumina ceramic substrates are obtained by mixing alumina with sintering aids to form a slurry, and then tape casting, debinding, and sintering. The alumina ceramic substrates obtained by this process have limited strength, are prone to warping, and have high roughness. The thermal conductivity is still a distance away from the theoretical performance. Therefore, it is of great significance to develop a new method to prepare alumina ceramic substrates with high strength, low warping, low roughness and high thermal conductivity. Summary of the invention

[0003] In view of this, an object of the present invention is to provide a method for preparing a high-performance alumina ceramic substrate, wherein the obtained ceramic substrate has good mechanical strength.

[0004] In order to achieve the above object, the present invention provides the following technical solutions: A method for preparing a high-performance alumina ceramic substrate comprises the following steps: S1: Mixing and dispersing: ball-milling and dispersing polyacrylic acid, sintered core material, composite adhesive and alumina to obtain a mixed slurry; S2: Casting, flattening and debonding: S3: Sintering: The debinded material is sent into a spark plasma sintering furnace and heated to 1550-1650°C for 30-50 minutes; S4: Cooling: Cooling the sintered body to room temperature.

[0005] Preferably, the weight ratio of the polyacrylic acid, the sintered core material, the composite adhesive and the aluminum oxide is 5:3:2:4.

[0006] Preferably, the method for preparing the sintered core material specifically comprises the following steps: Mix deionized water and polyvinyl alcohol, and stir at 40-50°C for 5-10 minutes to obtain a water phase; xylene, ethanol and polyethylene glycol were mixed and stirred for 20 minutes to obtain a first solvent phase; Mix chloroform and polylactic acid, stir at 50-60°C for 20-30 minutes, and cool to room temperature to obtain a second solvent phase; adding the second solvent phase into the first solvent phase to obtain a third solvent phase; The aqueous phase and the third solvent phase are mixed, and ultrasonic stirring is continued for 3-4 hours at 30-40° C., the stirring rate is 700-800 r / min, the ultrasonic time is 10-15 minutes, and the mixture is kept at a temperature for 1-2 hours, filtered, and dried to obtain a sintered core material.

[0007] Preferably, the weight ratio of the deionized water to the polyvinyl alcohol is 9:1; The weight ratio of xylene, ethanol and polyethylene glycol is 3:5:2; The weight ratio of chloroform to polylactic acid is 3:2; The weight ratio of the second solvent phase to the first solvent phase is 1:1; The weight ratio of the water phase to the third solvent phase is 1:3.

[0008] Preferably, the polyethylene glycol is polyethylene glycol 4000.

[0009] Preferably, the composite adhesive comprises acrylonitrile, ionic liquid and organic acid ester.

[0010] Preferably, the weight ratio of acrylonitrile, ionic liquid and organic acid ester is 5:1:1.

[0011] Preferably, the ionic liquid includes at least one of 1-ethyl-3-methylimidazolium methyl phosphate, 1-ethyl-3-methylimidazolium dihydrogen ammonium salt and 1-ethyl-2,3-dimethylimidazolium hexafluorophosphate.

[0012] Preferably, the organic acid ester includes at least one of isopropyl citrate, tributyl citrate and dioctyl azelate.

[0013] Preferably, the ball milling dispersion in step S1 specifically includes the following steps: a circulation frequency of 700-900 rpm, a diaphragm pump frequency of 50-60 Hz, a sand milling time of 1-2 h, and an ultrasonic frequency of 20-50 Hz.

[0014] The sintered core material of the present invention has a multi-gradient phase change effect through the addition of polyethylene glycol and polylactic acid. As the sintering proceeds, sufficient liquid organic matter can be released to prevent thermal runaway and adjust the mechanical properties of the ceramic substrate. In addition, the addition of polymer polyacrylic acid and composite adhesive can form a macromolecular chain liquid phase system, which is beneficial to the rearrangement and growth of aluminum oxide grains through the adsorption and bonding of aluminum oxide particles, and can increase the flexibility of the liquid phase system. At the same time, during the dispersion process, ultrasound is used to accelerate and improve the wettability of the macromolecular liquid phase system on the aluminum oxide particles and the surface bonding protection. Voids are generated in the process of forming the macromolecular liquid phase system, making the sintering denser and the strength better. DETAILED DESCRIPTION

[0015] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. In addition, it is specifically stated that the raw materials and equipment of the present invention can be obtained from commercial sources, and no longer listed one by one. Among them, the raw materials of the present invention can be obtained from commercial sources and are well known to those skilled in the art. Embodiment 1:

[0016] A method for preparing a high-performance alumina ceramic substrate comprises the following steps: S1: Mixing and dispersing: polyacrylic acid, sintered core material, composite adhesive and alumina are mixed in a weight ratio of 5:3:2:4 and dispersed by ball milling, with a circulation frequency of 700 rpm, a diaphragm pump frequency of 50 Hz, a sand milling time of 1 h, and an ultrasonic frequency of 20 Hz to obtain a mixed slurry; The preparation method of the sintered core material specifically includes the following steps: deionized water and polyvinyl alcohol are mixed in a weight ratio of 9:1, and stirred at 40°C for 5 minutes to obtain a water phase; xylene, ethanol and polyethylene glycol (polyethylene glycol 4000) are mixed in a weight ratio of 3:5:2, and stirred for 20 minutes to obtain a first solvent phase; chloroform and polylactic acid are mixed in a weight ratio of 3:2, stirred at 50°C for 20 minutes, and cooled to room temperature to obtain a second solvent phase; the second solvent phase is added to the first solvent phase in a weight ratio of 1:1 to obtain a third solvent phase; the water phase and the third solvent phase are mixed in a weight ratio of 1:3, and ultrasonic stirring is continued at 30°C for 3 hours, the stirring rate is 700r / min, the ultrasonic time is 10 minutes, the heat is kept and allowed to stand for 1 hour, filtered, and dried to obtain a sintered core material; The composite adhesive includes acrylonitrile, ionic liquid and organic acid ester, which is mixed in a weight ratio of 5:1:1; wherein the ionic liquid includes at least one of 1-ethyl-3-methylimidazolium methyl phosphate, 1-ethyl-3-methylimidazolium dihydrogen ammonium salt and 1-ethyl-2,3-dimethylimidazolium hexafluorophosphate; the organic acid ester includes at least one of isopropyl citrate, tributyl citrate and dioctyl azelate; S2: Casting, flattening and debonding: S3: Sintering: The debinded material is sent into a spark plasma sintering furnace and heated to 1550°C for 30 minutes; S4: Cooling: Cooling the sintered body to room temperature. Embodiment 2:

[0017] A method for preparing a high-performance alumina ceramic substrate comprises the following steps: S1: Mixing and dispersing: polyacrylic acid, sintered core material, composite adhesive and alumina are mixed in a weight ratio of 5:3:2:4 and dispersed by ball milling, with a circulation frequency of 900 rpm, a diaphragm pump frequency of 60 Hz, a sand milling time of 2 h, and an ultrasonic frequency of 50 Hz to obtain a mixed slurry; The preparation method of the sintered core material specifically includes the following steps: deionized water and polyvinyl alcohol are mixed in a weight ratio of 9:1, and stirred at 50°C for 10 minutes to obtain an aqueous phase; xylene, ethanol and polyethylene glycol (polyethylene glycol 4000) are mixed in a weight ratio of 3:5:2, and stirred for 20 minutes to obtain a first solvent phase; chloroform and polylactic acid are mixed in a weight ratio of 3:2, stirred at 60°C for 30 minutes, and cooled to room temperature to obtain a second solvent phase; the second solvent phase is added to the first solvent phase in a weight ratio of 1:1 to obtain a third solvent phase; the aqueous phase and the third solvent phase are mixed in a weight ratio of 1:3, and ultrasonic stirring is continued at 40°C for 4 hours, the stirring rate is 800r / min, the ultrasonic time is 15 minutes, the temperature is kept and allowed to stand for 2 hours, filtered, and dried to obtain a sintered core material; The composite adhesive includes acrylonitrile, ionic liquid and organic acid ester, which is mixed in a weight ratio of 5:1:1; wherein the ionic liquid includes at least one of 1-ethyl-3-methylimidazolium methyl phosphate, 1-ethyl-3-methylimidazolium dihydrogen ammonium salt and 1-ethyl-2,3-dimethylimidazolium hexafluorophosphate; the organic acid ester includes at least one of isopropyl citrate, tributyl citrate and dioctyl azelate; S2: Casting, flattening and debonding: S3: Sintering: The debinded material is sent into a spark plasma sintering furnace and heated to 1650°C for 50 minutes; S4: Cooling: Cooling the sintered body to room temperature. Embodiment 3:

[0018] A method for preparing a high-performance alumina ceramic substrate comprises the following steps: S1: Mixing and dispersing: polyacrylic acid, sintered core material, composite adhesive and alumina are mixed in a weight ratio of 5:3:2:4 and dispersed by ball milling, with a circulation frequency of 800 rpm, a diaphragm pump frequency of 55 Hz, a sand milling time of 1.5 h, and an ultrasonic frequency of 40 Hz to obtain a mixed slurry; The preparation method of the sintered core material specifically includes the following steps: deionized water and polyvinyl alcohol are mixed in a weight ratio of 9:1, and stirred at 45°C for 8 minutes to obtain a water phase; xylene, ethanol and polyethylene glycol (polyethylene glycol 4000) are mixed in a weight ratio of 3:5:2, and stirred for 20 minutes to obtain a first solvent phase; chloroform and polylactic acid are mixed in a weight ratio of 3:2, stirred at 55°C for 25 minutes, and cooled to room temperature to obtain a second solvent phase; the second solvent phase is added to the first solvent phase in a weight ratio of 1:1 to obtain a third solvent phase; the water phase and the third solvent phase are mixed in a weight ratio of 1:3, and ultrasonic stirring is continued at 35°C for 3.5 hours, the stirring rate is 750r / min, the ultrasonic time is 12 minutes, and the heat preservation is allowed to stand for 1.5 hours, filtered, and dried to obtain a sintered core material; The composite adhesive includes acrylonitrile, ionic liquid and organic acid ester, which is mixed in a weight ratio of 5:1:1; wherein the ionic liquid includes at least one of 1-ethyl-3-methylimidazolium methyl phosphate, 1-ethyl-3-methylimidazolium dihydrogen ammonium salt and 1-ethyl-2,3-dimethylimidazolium hexafluorophosphate; the organic acid ester includes at least one of isopropyl citrate, tributyl citrate and dioctyl azelate; S2: Casting, flattening and debonding: S3: Sintering: The debinded material is sent into a spark plasma sintering furnace and heated to 1600°C for 40 minutes; S4: Cooling: Cooling the sintered body to room temperature. Comparative Example 1

[0019] The preparation method of Comparative Example 1 is basically the same as that of Example 1, except that no sintered core material is used, specifically: A method for preparing a high-performance alumina ceramic substrate comprises the following steps: S1: Mixing and dispersing: polyacrylic acid, composite adhesive and alumina are mixed in a weight ratio of 5:3:2:4 and dispersed by ball milling, with a circulation frequency of 700 rpm, a diaphragm pump frequency of 50 Hz, a sand milling time of 1 h, and an ultrasonic frequency of 20 Hz to obtain a mixed slurry; The composite adhesive includes acrylonitrile, ionic liquid and organic acid ester, which is mixed in a weight ratio of 5:1:1; wherein the ionic liquid includes at least one of 1-ethyl-3-methylimidazolium methyl phosphate, 1-ethyl-3-methylimidazolium dihydrogen ammonium salt and 1-ethyl-2,3-dimethylimidazolium hexafluorophosphate; the organic acid ester includes at least one of isopropyl citrate, tributyl citrate and dioctyl azelate; S2: Casting, flattening and debonding: S3: Sintering: The debinded material is sent into a spark plasma sintering furnace and heated to 1550°C for 30 minutes; S4: Cooling: Cooling the sintered body to room temperature.

[0020] The following tests were conducted on Examples 1-3, the commercially available ceramic substrates produced by Shenzhen Jiarifeng Electronic Materials Co., Ltd., and the ceramic substrates obtained in Comparative Example 1.

[0021] Performance Testing: Warpage test: Use a parallel plate warpage instrument to measure the warpage of the ceramic substrate. The standard spacing of the parallel plates = the standard thickness of the substrate + the allowable warpage value (1.8‰). If the ceramic substrate passes between the parallel plates, it is considered to have passed the warpage test.

[0022] Roughness: Use a roughness meter to measure the roughness of the ceramic substrate.

[0023] Strength: The ceramic substrate is laser scribed into small plates of 24×40 mm, and then the substrate strength is tested by fracture extrusion using a universal electronic material testing machine.

[0024] Thermal conductivity: Using LFA467 thermal conductivity tester (10mm×2.0mm specification sample), the qualified thermal conductivity range is ≥170W / (m·K).

[0025] The warpage, roughness and strength were tested on 100 ceramic substrates, and the average value of the test results was taken.

[0026] Table 1: Test data of ceramic substrates of Examples 1-3, commercially available substrates and Comparative Example 1

[0027] It can be seen from the above table that the substrates prepared in Examples 1-3 have relatively good warpage, roughness, strength and thermal conductivity.

[0028] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a high-performance alumina ceramic substrate, characterized in that: The following steps are involved: S1: Mixing and dispersing: ball-milling and dispersing polyacrylic acid, sintered core material, composite adhesive and alumina to obtain a mixed slurry; S2: Casting, flattening and debonding: S3: Sintering: The debinded material is sent into a spark plasma sintering furnace and heated to 1550-1650°C for 30-50 minutes; S4: Cooling: Cooling the sintered body to room temperature.

2. The method for preparing a high performance alumina ceramic substrate according to claim 1, characterized in that: The weight ratio of the polyacrylic acid, the sintered core material, the composite adhesive and the aluminum oxide is 5:3:2:

4.

3. The method for preparing a high performance alumina ceramic substrate according to claim 2, characterized in that: The preparation method of the sintered core material specifically comprises the following steps: Mix deionized water and polyvinyl alcohol, and stir at 40-50°C for 5-10 minutes to obtain a water phase; xylene, ethanol and polyethylene glycol were mixed and stirred for 20 minutes to obtain a first solvent phase; Mix chloroform and polylactic acid, stir at 50-60°C for 20-30 minutes, and cool to room temperature to obtain a second solvent phase; adding the second solvent phase into the first solvent phase to obtain a third solvent phase; The aqueous phase and the third solvent phase are mixed, and ultrasonic stirring is continued for 3-4 hours at 30-40° C., the stirring rate is 700-800 r / min, the ultrasonic time is 10-15 minutes, and the mixture is kept at a temperature for 1-2 hours, filtered, and dried to obtain a sintered core material.

4. The method for preparing a high performance alumina ceramic substrate according to claim 3, characterized in that: The weight ratio of the deionized water to the polyvinyl alcohol is 9:1; The weight ratio of xylene, ethanol and polyethylene glycol is 3:5:2; The weight ratio of chloroform to polylactic acid is 3:2; The weight ratio of the second solvent phase to the first solvent phase is 1:1; The weight ratio of the water phase to the third solvent phase is 1:

3.

5. The method for preparing a high performance alumina ceramic substrate according to claim 4, characterized in that: The polyethylene glycol is polyethylene glycol 4000.

6. The method for preparing a high performance alumina ceramic substrate according to claim 1, characterized in that: The composite adhesive comprises acrylonitrile, ionic liquid and organic acid ester.

7. The method for preparing a high performance alumina ceramic substrate according to claim 6, characterized in that: The weight ratio of the acrylonitrile, the ionic liquid and the organic acid ester is 5:1:

1.

8. The method for preparing a high performance alumina ceramic substrate according to claim 6, characterized in that: The ionic liquid includes at least one of 1-ethyl-3-methylimidazolium methyl phosphate, 1-ethyl-3-methylimidazolium dihydrogen ammonium salt and 1-ethyl-2,3-dimethylimidazolium hexafluorophosphate.

9. The method for preparing a high performance alumina ceramic substrate according to claim 6, characterized in that: The organic acid ester includes at least one of isopropyl citrate, tributyl citrate and dioctyl azelate.

10. The method for preparing a high performance alumina ceramic substrate according to claim 1, characterized in that: The ball milling dispersion in step S1 specifically includes the following steps: a circulation frequency of 700-900 rpm, a diaphragm pump frequency of 50-60 Hz, a sand milling time of 1-2 h, and an ultrasonic frequency of 20-50 Hz.

Citation Information

Patent Citations

  • Preparation process of large-size high-purity ceramic substrate

    CN115231903A

  • High-purity high-strength aluminum oxide ceramic substrate and preparation method thereof

    CN115849885A

Cited By

  • Method for preparing 998 ceramic substrate through low-temperature sintering

    CN121135393A